ANALISIS STAKEHOLDER DALAM IMPLEMENTASI PROGRAM KARTU PRAKERJA PADA MASA PANDEMI COVID-19 DI DIKOTA PEKANBARU - Awalia Agustiana (JIA: Jurnal Ilmiah Administrasi, 2021)
The Pre-Employment Card Program is an Indonesian government program in the form of training fee assistance to the Indonesian people to improve their abilities or improve practical skills for the world of work. The pre-employment card program is a work competency development program aimed at job seekers, laborers who have been terminated, or who require competency improvement. The purpose of this study was to identify stakeholders in the implementation of the pre-employment card program during the covid-19 pandemic. The theory used is the theory of Reed et al (2009) in Nurfatriani et al., 2015 . This research method uses qualitative methods. Informants were taken using purposive and snowball sampling techniques, namely the determination of the sample based on considerations. This research uses interview, observation and documentation methods. The results of this study indicate that stakeholders in the implementation of the pre-employment card program during the covid -19 pandemic in the city of Pekanbaru have played their role well in the implementation of the pre-employment card program, but the lack of relationships between stakeholders in the form of communication and coordination. Keywords: Stakeholders, Pre-Employment Card Program, Covid-19.